Intervertebral Disc Maintenance and Repair Potential in Mice with Different Repair Potential. Issue 1 (April 2016) - Zhang, Ying; Xiong, Chi; Chan, Danny; Sakai, Daisuke
Introduction: Intervertebral disc (IVD) degeneration is a major cause of back pain, affecting quality of life. Current treatments are limited to salvage surgical operations. Biological treatments to relieve symptoms or restore disc are not available as we know little about the biology of disc degeneration and its potential to repair/regeneration. While most people will develop disc degeneration with aging, there are individuals who are protected even at old age, suggesting the presence of protective genes. Progenitor cells within the IVD are thought to play important roles in disc homeostasis. A hypothesis is that genetic factors can confer a protection against disc degeneration via better maintenance of endogenous progenitor cells. There exist strains of "healer" mice (LG/J, MRL/MpJ) with superior repair potential of cartilaginous tissues. We propose to study the maintenance of the IVD tissues in healer mice and assess potential relationship to progenitor cells, extracellular matrix and inflammatory response changes, to degeneration and repair/regeneration processes. Materials and Methods: "Healer" (MRL/MpJ) and "poor healer" (C57/BL6C) mice were used in this study. Histological comparison of tail disc was assessed from 8 to 24 weeks of age. Different NP cell populations and ECM markers were assessed using immunohistochemistry with specific cell markers. Tail-looping at 8-week of age for a fixed period was used as an environmental perturbation that will induce degeneration. Unlooping the tail after certain period of looping can assess repair processes with appropriate controls. Results: A comparison of MRL and C57 mice showed neither observable histological differences, nor signs of degenerative processes from 8-week to 24-week of age. Following tail looping for 4, 5, 6 and 8 weeks, there were significant distortion of the annulus fibrosus (AF) and NP at the compressed side, in terms of NP cell loss, AF tears and ruptures, and cell death in the AF. After the tails were unlooped for 4 weeks or 8 weeks, there were restorations of NP and AF structures in both strains of mice. However, superior repairing was seen in MRL mice at all time-points studied, in which the disc structure restored better via continuous expansion of NP region, cell repopulation and lamellae orientation recovered in the compressed AF sides with a clear NP-AF boundary. In C57 mice, the AF lamellae structure remained disorganized following unlooping. NP cell population analysis including Tie2, GD2, Sox9 and T showed different expression pattern in MRL and C57, from which showed that GD2 positive cells may be the functioning NP cell in disc maintenance. Besides, MRL maintained better Col I, Col II and aggrecan content during the repair processes. Interestingly, lower IL-1β was found in the "healer" mice, which suggested less inflammatory response may contribute to a better disc recovery after injury. Conclusion: By comparing the genetically different "healer" and "poor healer" mice, we showed a population of novel marked NP progentiors that may play important roles in the maintaining and repair/regenerative of IVD. The better repairing features in the "healer" mice are associated with better functional cell population maintenance and less inflammatory response. Acknowledgment: The project is supported by AOSPINE (SRN 2012_8), China's National Strategic Basic Research Program ("973") Grant 2014CB942901 and Research Grants Council of Hong Kong (T12–708/12N)